Suitability of Pre-Content and Post-Content of Indonesian Language Books for Grade V Students Based on BSNP Book Eligibility - Tsalistia Kurnia Larasati; Panca Dewi Purwati; Najma Hurinain Nifhan; Vita Kurnia Dewi; Jasmine Aisya Faza (STAI MA'ARIF MAGETAN, INDONESIA, 2025)
in Indonesian language books for fifth grade elementary school students based on the book eligibility standards set by the National Education Standards Agency (BSNP). This study uses a descriptive qualitative approach with a document analysis method on components such as the title page, foreword, table of contents, glossary, index, bibliography, and author profile. The results of the study indicate that in general the book has met the eligibility standards in terms of presentation structure, language, and graphics. However, several weaknesses were still found, such as inconsistencies in spelling, inconsistencies in page numbers in the table of contents, the use of sentences that are too complex for the level of understanding of elementary school students, and the lack of supporting visualizations in the post-content section. In addition, the author profile and bibliography do not show relevant and up-to-date sources. These findings emphasize the importance of attention to the pre-content and post-content sections so that textbooks not only meet the core material aspects but also support the effectiveness of learning in line with the principles of the Independent Curriculum.